DIFFERENCE BETWEEN PHRASAL NOUN AND PHRASAL VERB ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the intricate difference between Phrasal verbs and phrasal nouns, and concept of  both of them, their importance in English grammar. Many people know how to use them in grammar, but  they aren’t aware of difference of them. Phrasal noun and phrasal verb  make our speech more expressive and efficient. They are common in daily talk. Instead of  a long  sentence, we use them to express ideas clearly and fast.